ChemInform Abstract: A New Direct Synthesis of α‐Methylene‐ and α‐Alkylidene‐β‐lactams. Issue 33 (27th July 2016) - Hussein, Marwa; Nasr El Dine, Assaad; Fares, Fares; Dorcet, Vincent; Hachem, Ali; Gree, Rene
Abstract: The application of the Kinugasa reaction to alkynes bearing a nucleofuge in propargylic position gives a very direct entry to α‐methylene‐ and α‐alkylidene‐β‐lactams.